KARAKTERISTIK PENDERITA PENYAKIT JANTUNG KORONER YANG RAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2016-2017 - Juniarta Helmi F; Fazidah Siregar; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Coronary Heart Disease (CHD) is the first ranked cause of death world wide. The cause of deaths due to cardiovascular disease, especially coronary heart disease and stroke are expected to increase to 23.3 million deaths by 2030. Prevalence of CHD in Indonesia in 2013 is 0.5%. At  Santa Elisabeth Medan Hospital the proportion of CHD patients who hospitalized in 2010-2016 is 3,6% while case fatality rate is12,9%.. This is a descriptive study with case series design. The aims to identify characteristics of Coronary Heart Disease patients who hospitalized at Santa Elisabeth Medan Hospital in 2010-2016. Population is all of CHD patients and sample are 85 patient data. Data were analyzed descriptively. Bivariat analysis is using Chi Square, Mann Whitney and Kruskal Wallis test. The result shows that the largest proportion of CHD patients was 60-67 years old (25.9%), male (54.12%), Protestant Christian (69,4%), Bataknese (85.8%), housewife (30.7%), from Medan (68.2%), with complaints of chest / liver pain (49,4%), with normal diastolic blood pressure (64.7%), high blood sugar levels (42,4%), average length of stay at hospital is 5,45 days, outpatient home (67,1%), family expenditure (90,6%). There was a significant difference in proportion between  age by sex, average length of stay at hospital based on the condition when out of hospital. There was no significant difference in proportion between the average length of stay based on the source of cost. It was recommended that patients who have symptomps of CHD to get medical treatment immediately. For Santa Elisabeth Medan Hospital to complete the medical record such as blood sugar, total cholesterol, LDL, HDL, and triglycerides. Keywords: CHD, Patient Characteristics